Autonomy of philosophy of law in relation to metaphysics in Soloviov - Jakubiec, Marek (Hybris, 2015)
In the present paper two issues are enunciated. The first part consists brief analysis of Soloviov’s metaphysics. In the second one, main aspects of Russian philosopher’s legal theory and the relation between his metaphysical and legal conceptions are presented. The aim is to indicate originality of Soloviov’s thought, especially in the context of the paradigm which ruled in Russia in 19th century.